Turkey's Approach Towards Israel in the 1950s: Not Merely Following US policy - EKAVI ATHANASSOPOULOU (Middle Eastern Studies, 2017)
Within the context of Turkey's relationship with Israel, the 1950s are remembered largely as the decade when bilateral relations developed dramatically reflecting the US orientation of Adnan Menderes's foreign policy. On closer observation, however, one cannot fail to notice that there was more ebb than flow in Turkey's policy towards Israel which already assumed the double-faced profile (cold or reproachful in public/positive behind closed doors), which is usually associated with the next two decades. Drawing on substantial research in official US and British archives, this article explores the multiple considerations which informed the approach of the Menderes government towards Tel-Aviv. Crucially, it places the Turks’ approach within their broader Middle Eastern policy with the aim of showing that it was shaped not only by their relationship with their powerful ally, the United States, but also by the need to look after relations with neighbourly Arab regimes.